Intergranular Clay Films Control Inelastic Deformation in the Groningen Gas Reservoir: Evidence From Split‐Cylinder Deformation Tests. Issue 12 (17th December 2019) - Pijnenburg, R. P. J.; Verberne, B. A.; Hangx, S. J. T.; Spiers, C. J.
Abstract: Production of oil and gas from sandstone reservoirs leads to small elastic and inelastic strains in the reservoir, which may induce surface subsidence and seismicity. While the elastic component is easily described, the inelastic component, and any rate‐sensitivity thereof remain poorly understood in the relevant small strain range (≤1.0%). To address this, we performed a sequence of five stress/strain‐cycling plus strain‐marker‐imaging experiments on a single split‐cylinder sample (porosity 20.4%) of Slochteren sandstone from the seismogenic Groningen gas field. The tests were performed under in situ conditions of effective confining pressure (40 MPa) and temperature (100 °C), exploring increasingly large differential stresses (up to 75 MPa) and/or axial strains (up to 4.8%) in consecutive runs. At the small strains relevant to producing reservoirs (≤1.0%), inelastic deformation was largely accommodated by deformation of clay‐filled grain contacts. High axial strains (>1.4%) led to pervasive intragranular cracking plus intergranular slip within localized, conjugate bands. Using a simplified sandstone model, we show that the magnitude of inelastic deformation produced in our experiments at small strains (≤1.0%) and stresses relevant to the Groningen reservoir can indeed be roughly accounted for by clay film deformation. Thus, inelastic compaction of the Groningen reservoir is expected to be largely governed by clay film deformation. Compaction by this mechanism is shown to be rate insensitive on production timescales and is anticipated to halt when gas production stops. However, creep by other processes cannot be eliminated. Similar, clay‐bearing sandstone reservoirs occur widespread globally, implying a wide relevance of our results. Key Points: Triaxial tests on reservoir sandstone show uniform inelastic deformation at low strains (ε ≤ 1%) and localized deformation at high strains Low, uniform strains relevant to gas production are accommodated by deformation of intergranular clay films Reservoir compaction by this mechanism is expected to halt when gas production stops, though creep by other processes cannot be eliminated